2016
DOI: 10.1016/j.celrep.2016.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Th1 and Th17 in the Intestine Are Each Driven by Functionally Specialized Dendritic Cells with Distinct Requirements for MyD88

Abstract: Summary Normal dynamics between microbiota and dendritic cells (DCs) support modest numbers of T cells, yet these do not cause inflammation. The DCs that induce inflammatory T cells and the signals that drive this process remains unclear. Here we demonstrate that small intestine DCs lacking the signaling attenuator A20 induce inflammatory T cells and that the signals perceived and antigen presenting cell (APC) functions are unique for different DC subsets. Thus, while CD103+CD11b− DCs exclusively instruct IFNγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…CD103 + CD11b 2 DCs are unique cells that can cross-present Ag to CD8 + T cells (50). CD103 2 CD11b + DCs induce the differentiation of both IFN-g and IL-17-producing effector T cells (36,51,52). CD103 2 DCs, mainly composed of CD103 2 CD11b + DCs, are highly inflammatory during chronic colitis (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…CD103 + CD11b 2 DCs are unique cells that can cross-present Ag to CD8 + T cells (50). CD103 2 CD11b + DCs induce the differentiation of both IFN-g and IL-17-producing effector T cells (36,51,52). CD103 2 DCs, mainly composed of CD103 2 CD11b + DCs, are highly inflammatory during chronic colitis (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the P2X7 receptor abrogated the levels of these cytokines [113]. As ATP is presumed to be an important factor in the pathogenesis of inflammatory bowel disease [114,115], Atarashi et al administered ATP to mice and found that it exacerbated T-cell-mediated enterocolitis [116]. While P2X and P2Y receptors are expressed on many cells including myeloid and lymphoid cells [117], Liu et al have shown, using a microbiota antigen-specific T cell reporter mouse system, that TLR5 mediates the induction of intestinal Th17 cells by CD172α + lamina propria dendritic cells [115].…”
Section: Atpmentioning
confidence: 99%
“…There are three DC subsets in colon and all three were significantly reduced in C. rodentium infected Irgm1 -/mice (Fig 5f-h). The subsets most significantly affected were CD103 + CD11band CD103 -CD11b + DCs, both of which instruct intestinal Th1 responses [38][39][40][41]. CD103 -CD11b + DCs were unique in that their abundance was profoundly reduced in both infected and uninfected Irgm1 -/mice (Fig, 6f).…”
Section: Irgm1 Function Is Required To Support Cd4 T Cell Ifn Responmentioning
confidence: 98%
“…Colon lamina propria were processed as described [39] Briefly, colon was cut longitudinally and washed thoroughly to remove luminal contents. Colon was then cut into 0.3cm pieces and washed twice for 10 minutes in HBSS/10mM HEPES/0.035% NaHCO3/5mM EDTA/1.25% BSA/1mM DTT, followed by another 10 min wash in HBSS/10mM HEPES/0.035% NaHCO3/1.25%BSA.…”
Section: Preparation Of Colonic Lamina Propria and Immune Cell Phenotmentioning
confidence: 99%